Differences and Similarities the Role and Creative Agency of Producers in Pop, Rock and Classical - Tuomas Auvinen (Sweden, 2022)
Differences and similarities in the creative agency of the producer in the production process of urban pop music produced in a home studio, rock music produced in a conventional studio facility and classical concert hall music produced in a concert hall setting is explored in this paper. Starting from the premises of record production being a collaborative effort, I approach agency as the capacity to make and effect decisions within a structure or even to alter it to some extent, and creativity as contributing to the domain of existing works through exercising aesthetic decision-making. Based on these understandings of agency and creativity, I will examine how different cultures in different production settings and different studios conceived as cultural spaces affect the construction of the producer’s agency within creative communities in the production process. Furthermore, I will discuss how differences in understandings of the ontology of the music contribute to the level of creativity, i.e. the contribution to the domain of existing works, that a producer agent can possess. I base my presentation on extensive ethnographic fieldwork of three case studies on production processes, which took place in the course of 2015- 2017.
Proceedings of the 12th Art of Record Production Conference - Mono: Stereo: Multi